2024
DOI: 10.1146/annurev-ento-033023-015753
|View full text |Cite
|
Sign up to set email alerts
|

Biology, Ecology, and Management of Flea Beetles in Brassica Crops

Zhenyu Li,
Alejandro Carlos Costamagna,
Franziska Beran
et al.

Abstract: Brassica vegetable and oilseed crops are attacked by several different flea beetle species (Chrysomelidae: Alticini). Over the past decades, most research has focused on two Phyllotreta species, Phyllotreta striolata and Phyllotreta cruciferae, which are major pests of oilseed rape in North America. More recently, and especially after the ban of neonicotinoids in the European Union, the cabbage stem flea beetle, Psylliodes chrysocephala, has become greatly important and is now considered to be the major pest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 150 publications
(282 reference statements)
0
2
0
Order By: Relevance
“…The larvae feed inside petioles and stems through tunneling, while the adults feed on the leaves and cotyledons of the crops (Ortega-Ramos et al, 2022). Managing CSFB has become increasingly challenging due to the ban on neonicotinoid seed treatments and the emergence of pyrethroid-resistant populations, the primary insecticide group used against CSFB in Europe (Højland et al, 2015; Willis et al, 2020; Ortega-Ramos et al, 2022; Li et al, 2024). In a previous study, we showed that RNAi has the potential to control CSFB (Cedden et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The larvae feed inside petioles and stems through tunneling, while the adults feed on the leaves and cotyledons of the crops (Ortega-Ramos et al, 2022). Managing CSFB has become increasingly challenging due to the ban on neonicotinoid seed treatments and the emergence of pyrethroid-resistant populations, the primary insecticide group used against CSFB in Europe (Højland et al, 2015; Willis et al, 2020; Ortega-Ramos et al, 2022; Li et al, 2024). In a previous study, we showed that RNAi has the potential to control CSFB (Cedden et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…The cabbage stem flea beetle is an important pest of winter oilseed rape crops, particularly in northern Europe (Sivčev et al, 2016; Li et al, 2024). The larvae feed inside petioles and stems through tunneling, while the adults feed on the leaves and cotyledons of the crops (Ortega-Ramos et al, 2022).…”
Section: Introductionmentioning
confidence: 99%